Diversidade e estrutura genética de populações de mangabeira (Hancornia speciosa Gomes) nos tabuleiros costeiros do Nordeste do Brasil - MAIA, Ana Kelly dos Santos (2017)
The mangabeira (Hancornia speciosa Gomes) is a native fruit tree of Brazil, widely distributed in the cerrado and coastal boards. It produces tasty, nutritious and widely used fruits, with great potential for economic exploration. However, the natural populations of H. speciosa are undergoing an intense process of genetic erosion as a result mainly of expansion of agricultural frontier and cities, without study on diversity and genetic structure of populations. The lack of such information is limited to the adoption of efficient collect and conservation of genetic resources. The objective of this work was to analyze the diversity and genetic structure, as well as to infer the phylogeographic patterns of the natural populations of H. speciosa on Northeast Coastal Boards of Brazil. Microsatellite or SSR (six loci) and cpDNA (trnH-psbA region) markers were used to estimate the genetic diversity indexes and to get phylogeographic inferences of four natural populations of H. speciosa (96 individuals) sampled in the States of Maranhão, Paraíba, Pernambuco and Sergipe. The species showed moderate genetic structuring (FST = 0.095) with greater genetic diversity within populations (83%) than among populations (17%). The FST values for the pair of populations showed the smallest genetic differentiation between Paraíba x Pernambuco (0.015) and a larger between Maranhão and Pernambuco (0.142). It was observed that the Maranhão population had larger differentiation among four one. In general, for the populations studied, the fixation index was zero or negative (-0.082). A cpDNA analysis revealed six haplotypes and the Sergipe population presents a greater diversity of haplotypes, showing a haplotype in common with the States of Paraíba and Pernambuco. The population of Maranhão presents haplotypes exclusive. A spatial molecular variance analysis revealed two groups with high genetic structure (FST = 0.898 and FCT = 0.899), with 89.92% of the variation between the groups. This information on diversity and genetic structure are important subsidies for optimizing ex-situ and in-situ conservation of the genetic resources of mangabeira on studied region and for search of pre-breeding research of this species.